High-content Image-based Drug Testing of Patients’ Primary Fibroblasts Reveals Potential New Treatment Options for Localized Scleroderma - Katariina Mähönen; Isabel Mogollon; Antti Hassinen; Minttu Polso; Katja Välimäki; Swapnil Potdar; Al-Amin Chowdhury; Annamari Ranki; Jani Saarela; Vilja Pietiäinen; Jaana Panelius (Acta Dermato-Venereologica, 2025)
Localized scleroderma is a rare autoimmune disease characterized by progressive fibrosis of the skin and its underlying structures, causing loss of normal tissue structure and function. Myofibroblasts, differentiated from fibroblasts by high expression of α-smooth muscle actin, play a key role in the pathogenesis with continuous production of collagen and other extracellular matrix components. Transforming growth factor β promotes myofibroblast transformation and is central to the pathogenesis of fibrotic diseases. Targeted therapies for skin fibrosis are lacking, and current treatment consisting of topical steroids and immunosuppressive drugs often has limited efficacy. In this study, testing was performed with 78 drugs on lesional localized scleroderma fibroblasts to find potential new therapies, with α-smooth muscle actin and collagen-1 expression as markers for antifibrotic effect. Several drugs belonging to inhibitors of tyrosine kinase, phosphoinositide-3 kinase, and transforming growth factor β receptor were found to have an antifibrotic effect in localized scleroderma fibroblasts. Along with increased expression of transforming growth factor β1, Smad3, and AKT found in lesional localized scleroderma skin, these results confirm transforming growth factor β pathway as a treatment target. Additionally, androgen receptor antagonists showed potential antifibrotic effects, co-aligning with an increased expression of androgen receptor in localized scleroderma skin.